2009
DOI: 10.1002/adma.200901096
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabubble: A Laminated Ultrasound Contrast Agent with Narrow Size Range

Abstract: A laminated shell microcapsule is described resisting aggregation and withstanding ultrasound destruction, showing a good backscatter signal, as shown in the figure. Templated synthesis produces versatile monodisperse capsules <3 µm, with ultrasound‐pressure dependency allowing rupture above MI ∼ 1.5 (at 2 MHz), suitable for future development as both controlled‐delivery agent and contrast agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(121 citation statements)
references
References 22 publications
(37 reference statements)
1
118
0
2
Order By: Relevance
“…Currently, the particle sizes of synthesized HSSs are mainly in the sub-micrometer range [1][2][3] and only few literatures [12,13,21] reported the large particle sizes of HSSs (>1.0 lm) with smooth and compact silica shells due to the difficult control of the curvature effects of large templates and homogeneous nucleation in the coating process [22,23]. Therefore, to the best of our knowledge, the functionalized HSSs with micrometric particle size has rarely been fabricated.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Currently, the particle sizes of synthesized HSSs are mainly in the sub-micrometer range [1][2][3] and only few literatures [12,13,21] reported the large particle sizes of HSSs (>1.0 lm) with smooth and compact silica shells due to the difficult control of the curvature effects of large templates and homogeneous nucleation in the coating process [22,23]. Therefore, to the best of our knowledge, the functionalized HSSs with micrometric particle size has rarely been fabricated.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, most recent investigations have shown that the hollow silica microspheres have excellent echoing characteristic under ultrasonic radiation [21]. To evaluate the potential application of as-prepared amino functionalized HSMS as an ultrasound imaging contrast agent, the contrast-enhanced ultrasonography (CEUS) images of the HSMS with concentrations from 0 to 1.0 mg/mL were investigated as shown in Fig.…”
Section: In Vivo Ultrasound Imaging Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Elastically shelled microcapsules with organosilane compositions were initially found to enhance ultrasound resonance. [3] Later, additional boron and perfluoropentane (PFP) vapor were incorporated to strengthen shell robustness and scattering intensity. [4] More recently, a series of cell-level biological effects were also explored by using inorganic microcapsules as the ultrasound imaging agents.…”
Section: Doi: 101002/adma201104033mentioning
confidence: 99%
“…New developments in the fabrication processes to generate more controlled bubble properties could open up new ways of addressing many of the issues. So far, significant efforts have been made to manufacture bubbles with a very high degree of control over bubble uniformity in terms of their size and coating properties [132][133][134]. This would potentially help the accurate prediction of the acoustic response of a bubble population exposed to ultrasound given specific scanner settings.…”
Section: Concluding Remarks and Future Developmentmentioning
confidence: 99%